Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/jbc.m112.386441
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Activity of a Unique Sulfated Pyranosic (1→3)-β-l-Arabinan through Direct Interaction with Thrombin

Abstract: Background: Many seaweed polysaccharides have anticoagulant activity, but the mechanism of action was elucidated in a few cases. Results: A highly sulfated pyranosic ␤-arabinan exerts its activity through direct and indirect inhibition of thrombin. Conclusion:The structure and mechanism of action of the arabinan are different from those found for other polysaccharides. Significance: This arabinan could be an alternative anticoagulant in certain specific cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…Natural sulfated polysaccharides, such as galactans [3,4,5,6,7], arabinans [8], fucans [3,4,5,9], and fucoidans [3,6,10,11,12,13], present in seaweeds and invertebrates, are regarded as perspective inhibitors of blood coagulation and thrombosis. Influence of these biopolymers on the hemostatic system is determined by the ability of polymeric sulfates to interact with positively charged groups in proteins responsible for hemostasis, leading to the formation of stabilized complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural sulfated polysaccharides, such as galactans [3,4,5,6,7], arabinans [8], fucans [3,4,5,9], and fucoidans [3,6,10,11,12,13], present in seaweeds and invertebrates, are regarded as perspective inhibitors of blood coagulation and thrombosis. Influence of these biopolymers on the hemostatic system is determined by the ability of polymeric sulfates to interact with positively charged groups in proteins responsible for hemostasis, leading to the formation of stabilized complexes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies revealed certain structure-activity relationships for these macromolecules [3,6,8,11,12,14,15,16]. The main structural features of sulfated polysaccharides, which should be taken into account regarding their anticoagulant and antithrombotic properties, include the monosaccharide composition, the degree and pattern of sulfation, molecular weight, and types of glycosidic bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The similar mechanism of action was shown for the fucoidans from the brown seaweeds Saccharina latissima and F. distichus, but the polysaccharides from Cladosiphon okamuranus and Analipus japonicus were inactive [13]. Notably, a linear arabinan consisting of (1 → 3)-linked β-l-arabinose residues sulfated at C-2 and/or C-4 was also found to be the potent direct thrombin inhibitor [6].…”
Section: Introductionmentioning
confidence: 57%
“…Natural sulfated polysaccharides, such as galactans [1][2][3][4][5], arabinans [6], and fucoidans [1,4,[7][8][9][10][11], present in seaweeds, as well as sulfated fucans of invertebrates [1-3, 7, 12], are regarded as the perspective basis to develop drugs for different applications. Among these polysaccharides, the fucoidans raise the largest interest, as it can be concluded from the statistical records for corresponding papers summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Discovery of the anticoagulant activity of heparin has led not only to its widespread clinical use but also to the search for other highly-sulfated polysaccharides as heparin substitutes/supplanters-a search that is ongoing (Chen et al 2012;Fernández et al 2013) despite concurrent emphasis on direct thrombin inhibitors (Coppens et al 2012;Marson et al 2012). Heparin, a sulfated glycosaminoglycan in which the repeat unit is a disaccharide comprising α-L-iduronic acid-2-sulfate linked β-1,4 to Nsulfurylglucosamine-6-sulfate, exerts its therapeutic effect by catalyzing the antithrombin-mediated inhibition of various coagulation proteases (Björk and Lindahl 1982;Björk et al 1989).…”
Section: Introductionmentioning
confidence: 99%